Desenvolvimento tecnológico de extratos padronizados em ácido elágico das folhas de eugenia uniflora L. (Myrtaceae) - Assunção, Paulo Isaac Dias (2016)
Eugenia uniflora L. (Myrtaceae) is popularly known as Surinam cherry. According to popular usage, the tea leaves has application as an astringent, antidiarrheal, diuretic, antirheumatic, antipyretic, hypotensive, reducing blood cholesterol and controlling uric acid in the urine. Many of its therapeutic properties are validated by scientific researches. E. uniflora, for its medicinal importance, integrates RENISUS (National List of Medicinal Plants of Interest to the National Health System), highlighting the need for studies and research that could aid in the development of herbal medicines from this plant species. This study aimed at producing dry extracts by spraying from E. uniflora leaves, with a view to obtaining an intermediate for the production of herbal medicines and also to the acquisition parameters for quality control. The leaves of E. uniflora were obtained in the city of Anápolis-GO. Once identified, the material was dried and pulverized. For the acquisition of quality parameters was developed and validated a methodology for high-performance liquid chromatography (HPLC) for the evaluation of ellagic acid in the extracts. The liquid extract was obtained on a small scale by ultrasound assisted extraction (UAE) and the technique has been optimized using a Box Behnken design (33 ) for: alcoholic degree (%, w/w), time (minutes), and extraction temperature (°C) in the evaluation of ellagic acid concentration. The liquid extract on a larger scale was achieved by percolation of powdered material using ethanolic solution of 44% (w/w). The optimization of spray drying conditions evaluated the independent variables: inlet air temperature (°C), extract flow (mL/min.), and adjuvant concentration (% w/w), in function of the dependent variables: yield drying (%), moisture (%), water activity, and ellagic acid content (%, w/w) in a Box Behnken factorial design (33 ). The methodology developed was adequate for the evaluation of ellagic acid in the E. uniflora leaf extracts. The best conditions for UAE were: alcohol content of 44% (w/w), extraction time of 22 minutes, and extraction temperature of 59 °C. The content of ellagic acid was 93.7% ± 0.4% in relation to the predicted value. The drying parameters with higher desirability values were: inlet temperature of 144ºC, extract flow rate of 9 mL/min., and Aerosil® concentration of 49% (w/w). These conditions were checked in triplicate and presented responses in agreement with the values predicted by the model. The morphological evaluation of dried extracts optimized by scanning electron microscopy (SEM) revealed irregular particles of spherical shape and the observed diameters ranged between 1.08 and 10.548 micrometers.